Association of multiple preventive therapies postdischarge and long-term health outcomes after acute myocardial infarction. Issue 12 (2nd December 2021) - Chen, Chih-Wei; Lin, Yi-Cheng; Shih, Chun-Ming; Chen, Wan-Ting; Lin, Feng-Yen; Bi, Wei-Fung; Kao, Yung-Ta; Chiang, Kuang-Hsing; Chan, Chao-Shun; Hsu, Chien-Yi; Yang, Tsung-Lin; Hsiao, Cheng-Yi; et al.
Abstract : Background: Statins, beta-blockers, and angiotensin-converting enzyme inhibitors/angiotensin II receptor blockers have been advocated by guidelines as secondary prevention medications to improve the long-term outcomes of post-acute myocardial infarction (AMI) patients. However, adequate drug adherence has always been challenging, and different treatment regimens may lead to divergent outcomes that remain unclear under current myocardial infarction (MI) care standards. This study investigated the association between use of different preventive regimens post-AMI and patients' long-term outcomes. Methods: This cohort study used data files from the Taiwan National Health Insurance Research Database. A total of 77 520 people who were hospitalized with AMI between 2002 and 2015 were assessed. On the basis of medication possession ratio (MPR) to individual medications, eight treatment groups were examined in this study. Receiving therapy was defined as MPR ≥40%. We investigated the association between different treatment groups and all-cause mortality in 24 months. Results: Overall, 51 322 patients with ST-elevation MI and 26 198 with non-ST-elevation MI were included in the study. Patients received all three preventive medications show the lowest mortality in 24 months follow-up periods among all treatment groups. Patients who did not usage of any of these three preventive medications had the highest mortality in 24 months (adjusted hazard ratio, 1.78; 95% CI, 1.64-1.93). This mortality rate had the same pattern across the three cohort generations (2002-2005, 2006-2010, and 2011-2015). Conclusion: In this large population-based real-world study, usage of three preventive therapies post-MI was associated with the lowest rate of all-cause mortality.